An oncogenic CTNNB1 mutation is predictive of post-operative recurrence-free survival in an EGFR-mutant lung adenocarcinoma. - Yeseul Kim; Bokyung Ahn; Shinkyo Yoon; Goeun Lee; Deokhoon Kim; Sung-Min Chun; Hyeong-Ryul Kim; Se Jin Jang; Hee Sang Hwang (PLoS ONE, 2023)
The Wnt/β-catenin pathway is known to be frequently dysregulated in various human malignancies. Alterations in the genes encoding the components of Wnt/β-catenin pathway have also been described in lung adenocarcinoma. Notably however, the clinical impacts of Wnt/β-catenin pathway alterations in lung adenocarcinoma have not been fully evaluated to date. We here investigated the prognostic implications of single gene variations in 174 cases of surgically resected lung adenocarcinoma tested using targeted next-generation sequencing. Screening of the prognostic impact of single gene alterations identified an association between CTNNB1 mutation and poor recurrence-free survival in EGFR-mutant LUADs. Based on these results, the entire cohort was stratified into three groups in accordance with the mutational status of Wnt/β-catenin pathway genes (i.e. oncogenic CTNNB1 mutation [CTNNB1-ONC], other Wnt/β-catenin pathway gene mutations [Wnt/β-catenin-OTHER], and wild type for Wnt/β-catenin pathway genes [Wnt/β-catenin-WT]). The clinicopathologic characteristics and survival outcomes of these groups were then compared. Oncogenic CTNNB1 and other Wnt/β-catenin pathway gene mutations were identified in 10 (5.7%) and 14 cases (8.0%), respectively. The CTNNB1-ONC group cases displayed histopathologic features of conventional non-mucinous adenocarcinoma with no significant differences from those of the other groups. Using β-catenin immunohistochemistry, we found that the CTNNB1-ONC group displayed aberrant nuclear staining more frequently, but only in 60% of the samples. The LUADs harboring a CTNNB1-ONC exhibited significantly poorer RFS outcomes than the other groups, regardless of the β-catenin IHC status. This was a pronounced finding in the EGFR-mutant LUADs only in subgroup analysis, which was then confirmed by multivariate analysis. Nevertheless, no significant OS differences between these Wnt/β-catenin groups were evident. Hence, oncogenic CTNNB1 mutations may be found in about 6% of lung adenocarcinomas and may predict post-operative recurrence in EGFR-mutant LUADs. Aberrant nuclear β-catenin staining on IHC appears to be insufficient as a surrogate marker of an oncogenic CTNNB1 mutation.